Stem Cells and Acellular Preparations in Bone Regeneration/Fracture Healing: Where are We Now? - Marcel G. Brown; Davis J. Brady; Kelsey M. Healy; Kaitlin A. Henry; Ayobami S. Ogunsola; Xue Ma (Achievements and Challenges of Medicine and Medical Science Vol. 8, 2024)
The term ‘stem cell’ (stammzelle) was first introduced into the scientific community in the late 19th century by zoologists Theodor Boveri and Valentin Häcker, who proposed the existence of a universal precursor cell for both primordial germ and somatic cells. Bone/fracture healing is a complex process with different steps and four basic tissue layers being affected: cortical bone, periosteum, fascial tissue surrounding the fracture, and bone marrow. Stem cells and their derivatives, including embryonic stem cells, induced pluripotent stem cells, mesenchymal stem cells, hematopoietic stem cells, skeletal stem cells, and multipotent stem cells, can function to artificially introduce highly regenerative cells into decrepit biological tissues and augment the healing process at the tissue level. Stem cells are molecularly and functionally indistinguishable from standard human tissues. The widespread appeal of stem cell therapy lies in its potential benefits as a therapeutic technology that, if harnessed, can be applied in clinical settings. There are many challenges associated with stem cell therapy including differentiating stem cells into a desired cell line and the risk of stem cells developing into cancerous cell lines. Stem cells also carry a risk of being rejected by the host immune system whether they be allogeneic or autologous in nature. Beyond the cellular preparations, there exists acellular therapies, many of which have made their own contribution to the field of stem cell therapy. The ability of acellular preparations to harness the potential of growth factors through extracellular vesicles or secretomes provides many new and promising opportunities. The role of paracrine signaling as it relates to stem cell therapy for example is critical in making acellular solutions all the more viable as a therapy. Clinically, autologous bone grafting remains the standard for repairing bone defects. As stem cell engineering has evolved however, an increasing number of clinical trials have utilized bone marrow-derived mesenchymal stem cells with a shift towards greater utilization of umbilical cord-derived stem cells, amniotic stem cells (ASCs) and induced pluripotent stem cell (iPSC) therapies. These treatments have provided varying levels of healing in the spine, long bone fractures, facial bone fractures and even hip arthroplasty patients with bone healing defects. Many preclinical models have highlighted the use of these human pluripotent stem cells including both small and large animal models. Multipotent stem cells including hematopoietic, mesenchymal and even skeletal stem cells, have also shown increasing efficacy in many preclinical models. This review aims to establish the molecular pathophysiology of bone healing, the current stem cell interventions that disrupt or augment the bone healing process, and finally, consider the future direction/therapeutic options related to stem cells and bone healing. Understanding the mechanism, applications and therapeutic evidence behind current stem cell interventions will allow better implementation of these therapies through more preclinical and clinical trials with the eventual goal of meaningful clinical intervention.